BrFLC2 (FLOWERING LOCUS C) as a candidate gene for a vernalization response QTL in Brassica rapa - Zhao, Jianjun (Oxford University Press, 2010)
Flowering time is an important agronomic trait, and wide variation exists among Brassica rapa. In Arabidopsis, FLOWERING LOCUS C (FLC) plays an important role in modulating flowering time and the response to vernalization. Brassica rapa contains several paralogues of FLC at syntenic regions. BrFLC2 maps under a major flowering time and vernalization response quantitative trait locus (QTL) at the top of A02. Here the effects of vernalization on flowering time in a double haploid (DH) population and on BrFLC2 expression in selected lines of a DH population in B. rapa are descibed. The effect of the major flowering time QTL on the top of A02 where BrFLC2 maps clearly decreases upon vernalization, which points to a role for BrFLC2 underlying the QTL. In all developmental stages and tissues (seedlings, cotyledons, and leaves), BrFLC2 transcript levels are higher in late flowering pools of DH lines than in pools of early flowering DH lines. BrFLC2 expression diminished after different durations of seedling vernalization in both early and late DH lines. The reduction of BrFLC2 expression upon seedling vernalization of both early and late flowering DH lines was strongest at the seedling stage and diminished in subsequent growth stages, which suggests that the commitment to flowering is already set at very early developmental stages. Taken together, these data support the hypothesis that BrFLC2 is a candidate gene for the flowering time and vernalization response QTL in B. rapa.